Abundancia poblacional y beneficios económicos de la caza de animales silvestres en el área de conservación regional Ampiyacu Apayacu y su zona de influencia Loreto Perú - Puertas Melendez, Pablo Eloy (2025)
This study assesses hunting dynamics before and after the implementation of a wildlife management plan under co-management with local communities along the Ampiyacu and Yaguasyacu rivers, in the northeastern Peruvian Amazon, during the period 2016–2023. The main objective was to establish a sustainable management model for game species, which are highly relevant for local food security and household economy. A combination of participatory and non-participatory methodologies was applied, including semi-structured interviews, hunting records, hunting effort estimation, line transect censuses, and the unified harvest technique. Results show statistically significant differences in the hunting effort index (one-way ANOVA, F1,14=55.3024, p<0.0001), indicating increased abundance and accessibility of game species after the plan’s implementation. Furthermore, hunting focused on species with higher susceptibility and adequacy for sustainable harvest. Economically, the plan generated a total benefit of S/. 187,245 (US $51,200), with Cuniculus paca providing the highest biomass contribution and economic value of S/. 112,806 (US $30,783). These findings confirm the effectiveness of the plan as a sustainable management strategy, generating positive outcomes in both conservation and community income. It is recommended that governmental authorities promote participatory wildlife management policies, supported by robust monitoring methodologies that integrate line transects and camera traps to obtain more accurate estimates of population density and dynamics.